2019
DOI: 10.3390/app9091866
|View full text |Cite
|
Sign up to set email alerts
|

Loitering Detection Based on Pedestrian Activity Area Classification

Abstract: Loitering detection can help recognize vulnerable people needing attention and potential suspects harmful to public security. The existing loitering detection methods used time or target trajectories as assessment criteria, and only handled some simple loitering circumstances because of complex track. To solve these problems, this paper proposes a loitering detection method based on pedestrian activity area classification. The paper first gave loitering definition from a new perspective using the size of pedes… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 11 publications
(9 citation statements)
references
References 47 publications
0
7
0
Order By: Relevance
“…Their system monitors the individuals and applies a Generalized Sequential Patterns (GSP) algorithm to detect predefined patterns of repeated actions that characterize loitering. Huang et al [14] have proposed an approach that detects loitering based on pedestrian activity area fitting within three categories i.e., rectangle, ellipse, and sector loitering. The type of loitering is determined by trajectory maps and analyzing the suspicious target trajectory.…”
Section: Traditional Methodsmentioning
confidence: 99%
See 4 more Smart Citations
“…Their system monitors the individuals and applies a Generalized Sequential Patterns (GSP) algorithm to detect predefined patterns of repeated actions that characterize loitering. Huang et al [14] have proposed an approach that detects loitering based on pedestrian activity area fitting within three categories i.e., rectangle, ellipse, and sector loitering. The type of loitering is determined by trajectory maps and analyzing the suspicious target trajectory.…”
Section: Traditional Methodsmentioning
confidence: 99%
“…Similarly, concerning movement type, Huang et al [14] have found loitering to be a case of movement that forms a certain motion trajectory within a specific activity area. In this way, the following cases are possible: i.…”
Section: Loiteringmentioning
confidence: 99%
See 3 more Smart Citations